The Inheritance Rights Of Children From Marriage Are Not Recorded According To The Marriage Law And The Compilation Of Islamic Law - Wahidin, Jenal; Farid, Diana; Abdulah Pakarti, Muhammad Husni; Fathiah, Iffah; Mabruri, Kemal Al Kautsar (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
This research focuses on the inheritance rights of children from unregistered marriages in the Compilation of Islamic Law. Although marriages are supposed to be registered, situations where they are not recorded can have an impact on the inheritance rights of children. This research uses a qualitative research method with a normative juridical approach that is carried out based on legislation, which in this case includes the Civil Code, Law No. 1 of 1974. Data is obtained from sources of Law, Civil Code and journals. Data analysis is carried out to filter the data obtained and collected according to its type and finally draw conclusions from the findings obtained. The results show that children from irri marriages previously only received inheritance from the mother and the mother's family. However, the decision of the Constitutional Court allows extra-marital children to inherit from their biological father if legally proven. The Compilation of Islamic Law states that children from irri marriages only have a nasab relationship with the mother and her family, not with the father. Parents can apply for itsbat nikah to confirm the legal relationship, providing inheritance protection. However, if itsbat nikah is rejected, the child is not entitled to receive inheritance from the father. In conclusion, children from irri marriages have inheritance rights depending on the legal recognition of the relationship with their parents.